ChemInform Abstract: Applications of Sodium Borohydride Procedure for the Reductive Removal of Evans and Other Chiral Auxiliaries. Issue 10 (February 2016) - Prashad, Mahavir; Shieh, Wen‐Chung; Liu, Yugang
Abstract: Review: 73 refs.